พฤติกรรมการตักบาตรและถวายภัตตาหาร เพื่อสุขภาพที่ดีของพระสงฆ์ - ลลิลทิพย์ ธนสมบัตินันท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This article aims to analyze beliefs and practices of Buddhist regarding almsgiving and food offering to monks, monks’ eating behaviors and appropriate way of almsgiving and food offering, and proper diet that are beneficial to monk’s health. Researcher collected data through documentary and field research, which includes participant observation, in-depth interview, and data analysis.The research found that Buddhists’ practices toward almsgiving and food offering to monks is related to the realization of "Merit" and "cycle of birth and death". Nowadays, health awareness is taken the lead, resulting mostly Buddhist to use a good quality of material and to choose menu base on their preference for the almsgiving and food offering. The eating behavior altogether with health concern of monk is the main factor to their monks’ health problem.The healthiness of monks can be created when three factors were met. First, Buddhists concern more about quality of foods offering to monks. Second, Monks should deliberately think what to eat, exercise more, exempt consume the bad thing (e.g. energy drink, cigarettes), take a good care of mind and body, check-up on regular basis and seeing doctor when get sick. Third, Seller should aware the quality and freshness of material that will sell to Buddhist.In summarize, almsgiving and food offering with good food will contribute to monks’ healthy and to maintain the healthiness; monks have to have a health awareness. As a results, Buddhist will get the maximize return from merit whereas monks can enhance their working performance of social development and Buddhism advocation.